2009
DOI: 10.3899/jrheum.080907
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin in Patients with Active, Early, and Chronic Rheumatoid Arthritis Who Are Steroid- and Disease-Modifying Antirheumatic Drug-Naive Compared with Patients with Osteoarthritis and Controls

Abstract: Both early DMARD-naive and chronic RA were associated with higher plasma adiponectin compared to healthy controls, but lower plasma adiponectin than OA. Adiponectin increased 13% during MTX treatment. In patients with RA and OA body mass index, age, sex, and disease activity measures failed to explain the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 40 publications
4
62
2
5
Order By: Relevance
“…Clinically, adiposity is also associated with tendinopathy (42), and adipokines, such as leptin and adiponectin, have been associated with OA (43,44). Furthermore, another adipokine (visfatin) has been found to be associated with upper-extremity pain intensity (21) and with predicting recovery following upper-extremity injury.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, adiposity is also associated with tendinopathy (42), and adipokines, such as leptin and adiponectin, have been associated with OA (43,44). Furthermore, another adipokine (visfatin) has been found to be associated with upper-extremity pain intensity (21) and with predicting recovery following upper-extremity injury.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin has been found to be higher in RA patients than in healthy controls (34,(77)(78)(79)(80)(81). Moreover, adiponectin levels are increased in early RA patients that had never taken disease-modifying antirheumatic drugs and in chronic RA patients (82). Circulating adiponectin levels correlate with the severity of RA evaluated by joint destruction and radiographic damage (83,84).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 99%
“…In patients with chronic RA, Laurberg et al reported that methotrexate increases adiponectin levels (82). However, in anti-TNF therapy of RA patients, different authors reported contradictory results: unchanged adiponectin levels (37,86,87), increased levels (88 -91), and decreased levels in combination with corticoids (92).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic role of adiponectin is largely unknown in concern to RA and OA. Recent data proved that in chronic RA patients adiponectin plasma levels are higher compared to healthy controls, but lower plasma levels than in OA (Laurberg et al, 2009). Another member of this group is resistin (FIZZ3) which is found in adipocytes, macrophages and other cell types.…”
Section: Adipokines As Potential Participants In Oamentioning
confidence: 99%